Respiratory dendritic cell subsets differ in their capacity to support the induction of virus-specific cytotoxic CD8+ T cell responses. - Taeg S Kim; Thomas J Braciale (PLoS ONE)
Dendritic cells located at the body surfaces, e.g. skin, respiratory and gastrointestinal tract, play an essential role in the induction of adaptive immune responses to pathogens and inert antigens present at these surfaces. In the respiratory tract, multiple subsets of dendritic cells (RDC) have been identified in both the normal and inflamed lungs. While the importance of RDC in antigen transport from the inflamed or infected respiratory tract to the lymph nodes draining this site is well recognized, the contribution of individual RDC subsets to this process and the precise role of migrant RDC within the lymph nodes in antigen presentation to T cells is not clear. In this report, we demonstrate that two distinct subsets of migrant RDC--exhibiting the CD103(+) and CD11b(hi) phenotype, respectively--are the primary DC presenting antigen to naïve CD4(+) and CD8(+) T lymphocytes in the draining nodes in response to respiratory influenza virus infection. Furthermore, the migrant CD103(+) RDC subset preferentially drives efficient proliferation and differentiation of naive CD8(+) T cells responding to infection into effector cells, and only the CD103(+) RDC subset can present to naïve CD8(+) T cells non-infectious viral vaccine introduced into the respiratory tract. These results identify CD103(+) and CD11b(hi) RDC as critical regulators of the adaptive immune response to respiratory tract infection and potential targets in the design of mucosal vaccines.